Analisis pola asuh orangtua pada anak korban kekerasan dalam rumah tangga - Triave Nuzila Zahri; Lia Mita Syahri; Annisa Fujiyanti; Aulia Ulfani Marta Putri (Indonesian Institute for Counseling, Education and Theraphy, 2022)
Parents are the main place for children to get the things they need, starting from affection, a sense of security, a place for children to know about the world for the first time, but the reality is that not all parents are able to fulfill this, it is found that there are parents who are building family in an inappropriate way, such as physical or psychological violence that they do. This makes children victims of violence by parents. So the purpose of this study is to identify and analyze parenting styles for children who are victims of domestic violence. Regarding the population in this study were children who were victims of domestic violence with a sample of 40 children using simple random sampling technique. The findings of this study found that the type of parenting style ofauthoritarian parents became the parenting style carried out by parents who carried out acts of domestic violence with a percentage level of 50.62% which tended to be authoritarian parenting styles which were dominant parents and there was an element of violence in the development of children, so that services Guidance and counseling is expected to help child victims of domestic violence in overcoming difficult times or obstacles they feel as a result of the violence that has occurred.